THE EFFECT OF FEAR MOTIVATION ON EMPLOYEE PERFORMANCE AT PT. METROPOLITAN RADAR MEDIA - Hablil Ikhwana (PT Inovasi Pratama Internasional, 2022)
This study was conducted to reveal whether there is an influence of fear motivation on performance at PT. Media Radar Metropolitan Medan and how much influence. The research method used was by giving a questionnaire containing a questionnaire to 42 people who were sampled. The research conducted found the fact that there was a positive and significant influence between the influence of fear motivation on performance at PT. Media Radar Metropolitan Medan is evident from the value of t table = 2.021 and t count = 3.365 . t test results show t table > t count or significant is 0.002 < = 0.05 . This means that fear motivation has a significant effect on employee performance at a significant level = 5%. Significant means that H1 is accepted and Ho is rejected, meaning that partially there is a positive and significant influence and fear of motivation on employee performance. The percentage of the influence of fear motivation on performance at PT. Media Radar Metropolitan Medan is in accordance with the R square number of 0.318, meaning that 31.8% of the Dependent Variable (Employee Performance) is explained by the Independent Variable (Fear motivation), and the remaining 68.2% (100% - 31.8%) is explained by other variables excluding the variables used. According to the author, another factor that affects employee performance is the Occupational Health and Safety Management System (SMK3).